A tale of two basins: An integrated physical and biological perspective of the deep Arctic Ocean. (December 2015) - Bluhm, B.A.; Kosobokova, K.N.; Carmack, E.C.
Highlights: Basin circulation involves distinct surface, halocline, Atlantic and Deep Water layers. Water mass assemblies in the basins differ by the presence/absence of Pacific Water. Despite ridges, non-expatriate pelagic and benthic communities differ more with depth than horizontally. Changes include thinner sea ice retreating past the shelf break and stronger freshwater stratification. Vertical nutrient, primary production and organic matter flux is constrained by stratification. Wind forcing along ice-free shelf-breaks increases upwelling and production on shelves. Abstract: This review paper integrates the current knowledge, based on available literature, on the physical and biological conditions of the Amerasian and Eurasian basins (AB, EB) of the deep Arctic Ocean (AO) in a comparative fashion. The present day (Holocene) AO is a mediterranean sea that is roughly half continental shelf and half basin and ridge complex. Even more recently it is roughly two thirds seasonally and one third perennially ice-covered, thus now exposing a portion of basin waters to sunlight and wind. Basin boundaries and submarine ridges steer circulation pathways in overlying waters and limit free exchange in deeper waters. The AO is made integral to the global ocean by the Northern Hemisphere Thermohaline Circulation (NHTC) which drives Pacific-origin water (PW) through Bering Strait into the Canada Basin, and counter-flowing Atlantic-origin water (AW) through Fram Strait and across the Barents Sea into the Nansen Basin. As a framework for biogeography within the AO, four basic, large-scale circulation systems (with L > 1000 km) are noted; these are: (1) the large scale wind-driven circulation which forces the cyclonic Trans-Polar Drift from Siberia to the Fram Strait and the anticyclonic Beaufort Gyre in the southern Canada Basin; (2) the circulation of waters that comprise the halocline complex, composed largely of waters of Pacific and Atlantic origin that are modified during passage over the Bering/Chukchi and Barents/Siberian shelves, respectively; (3) the topographically-trapped Arctic Circumpolar Boundary Current (ACBC) which carries AW cyclonically around the boundaries of the entire suite of basins, and (4) the very slow exchange of Arctic Ocean Deep Waters. Within the basin domain two basic water mass assemblies are observed, the difference between them being the absence or presence of PW sandwiched between Arctic Surface Waters (ASW) above and the AW complex below; the boundary between these domains is the Atlantic/Pacific halocline front. Both domains have vertical stratification that constrains the transfer of nutrients to the surface layer (euphotic zone), thus leading to their oligotrophic state, particularly in the more strongly stratified Pacific Arctic where, despite high nutrient values in the inflow, convective reset of surface layer nutrients by haline convection in winter is virtually absent. First and multi-year sea ice drastically alters albedo and insulates the underlying water column from extreme winter heat loss while its mechanical properties (thickness, concentration, roughness, etc.) greatly affect the efficiency of momentum transfer from the wind to the underlying water. Biologically, sea ice algal growth in the basins is proportionally almost equal to or exceeding phytoplankton production, and is a habitat and transport platform for sympagic (ice-associated) fauna. Owing to nutrient limitation due to strong stratification and light limitation due to snow and ice cover and extreme sun angle, primary production in the two basin domains is very low compared to the adjacent shelves. Severe nutrient limitation and complete euphotic zone drawdown in the AB favors small phytoplankton, a ubiquitous deep chlorophyll maximum layer, a low f-ratio of new to recycled carbon fixation, and a low energy food web. In contrast, nutrients persist –albeit in low levels– in the western EB, even in summer, suggesting light limitation, heavy grazing or both. The higher stocks of nutrients in the EB are more conducive to marginal ice blooms than in the AB. The large-scale ocean currents (NHTC and ACBC) import substantial expatriate, not locally reproducing zooplankton biomass especially from the adjoining subarctic Atlantic (primarily Calanus finmarchicus ), but also from the Pacific (e.g., Pseudocalanus spp., Neocalanus spp . and Metridia pacifica ). These advective inputs serve both as source of food to resident pelagic and benthic biota within the basins, and as potential grazers exerting top down control on limited phytoplankton resources. Benthic organisms within the AO basin show previously unappreciated biodiversity and surprising dispersion of species given the isolation of individual basins and low vertical carbon flux and resulting biomass. Larval dispersion is aided by the large-scale flows and perhaps, we hypothesize in the deep benthos by convective updrafts driven by geothermal heating. Zooplankton diversity, in contrast, is low, but again faunal assemblages are equally distributed between the EB and AB. Species pools of both pelagic and benthic communities change more with water depth rather than laterally, with the exception of expatriates and rare species, with close ties to today's North Atlantic biogeographic region. Climate related change in the AO is thus manifest at significantly differing time scales. Throughout ∼90% of the Pleistocene the AO has existed in glacial mode, with narrow continental shelves, greatly restricted river inflow, thicker and perhaps immobile sea ice, and total blockage of exchange with the Pacific Ocean. During the Holocene, on shorter time scales of 1000–100 years, significant changes in high latitude climate are tied to changes in temperature and perhaps moisture delivery patterns. The Arctic also experiences significant multi-decadal variability; however, the pace of change over the past three decades has been without precedent. Within the basin interior the ice is now thinner and less compact, and thus more responsive to wind stress (forcing and mixing). Concurrent with sea ice melt and increased river flow, the accumulation of fresh water and the stratification have increased, thus constraining vertical nutrient flux affecting phytoplankton size distributions, limiting primary production in parts of the basins now and likely in the future, and increasing vulnerability to acidification. In addition, sea ice is now retreating on an annual basis past the shelf break, exposing basin waters directly to sunlight and wind forcing. Thus, upwelling favorable winds (generally from east to west) can now directly and efficiently drive shelf-break upwelling, and draw nutrients from subsurface basin waters onto the shelf; at the same time upwelling favorable winds will also create onshore pressure gradients over the slope and basin which will act to slow or block the flow of waters in the ACBC, and thus alter advective pathways of both abiotic and biotic materials. Given the opening of a new ocean to multiple user groups, we expect that the central AO will play an increasing larger role both in the research and political arenas in the future, and we encourage pan-Arctic international collaboration over focus on territorial boundaries.